2015
DOI: 10.1016/j.amepre.2014.10.011
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Effectiveness Analysis of the First Federally Funded Antismoking Campaign

Abstract: Background In 2012, CDC launched the first federally funded national mass media antismoking campaign. The Tips From Former Smokers (Tips) campaign resulted in a 12% relative increase in population-level quit attempts. Purpose Cost-effectiveness analysis was conducted in 2013 to evaluate Tips from a funding agency’s perspective. Methods Estimates of sustained cessations; premature deaths averted; undiscounted life years (LYs) saved; and quality-adjusted life years (QALYs) gained by Tips were estimated. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
62
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 27 publications
2
62
0
Order By: Relevance
“…Future research and economic modelling34 may be useful to further hone the application of these findings to future campaigns. Because we focused solely on cigarettes, evaluation of future campaigns that include other tobacco products may be useful.…”
Section: Resultsmentioning
confidence: 96%
“…Future research and economic modelling34 may be useful to further hone the application of these findings to future campaigns. Because we focused solely on cigarettes, evaluation of future campaigns that include other tobacco products may be useful.…”
Section: Resultsmentioning
confidence: 96%
“…Several studies evaluated wider tobacco control interventions 39, 44, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, whereas five studies included both smoking cessation programmes and tobacco control interventions 89, 90, 91, 92, 93.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 23 of 64 studies reported QALY as their main outcome 5, 35, 38, 40, 41, 47, 48, 49, 56, 58, 59, 61, 62, 63, 65, 69, 70, 76, 78, 81, 86, 88, 94, followed by life years (LY) gained ( n  = nine of 64) 33, 43, 46, 66, 67, 68, 73, 74, 89 or a combination of these ( n  = 12 of 64) 4, 6, 35, 36, 37, 39, 42, 44, 57, 77, 80, 83. Five of 64 studies reported disability adjusted life years (DALY) as their main outcome 60, 82, 90, 91, 92, and only four of 64 (incremental) net benefit 52, 53, 55, 71.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors can affect quit attempts [5], including substantial increases in price and taxation [13], but as noted in the Introduction the last substantial national increase in cigarette prices was during the first half of 2009, limiting changes in price as a simple explanation for the phenomenon. The CDC Tips from Former Smokers (TIPS) campaign started in the first half of 2012, and pre-post analyses of population cohorts has demonstrated that TIPS increases quit efforts [14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%